2022
DOI: 10.1186/s12909-022-03833-6
|View full text |Cite
|
Sign up to set email alerts
|

Has the COVID-19 pandemic affected nursing students’ career self-efficacy and professional calling? The mediating impact of professional identity

Abstract: Background Professional calling (PC) is crucial for ascertaining their professional goals and fulfilling career choices in nursing students. Thus, understanding its antecedents and helping schools improve PC among nursing students is critical. This study aims to explore whether professional identity (PI), as a crucial antecedent of PC, acts as an intermediary between career self-efficacy (CSE) and professional calling during the COVID-19 pandemic. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The results were similar to another Chinese research [ 26 ], which indicated that the average score of calling among nursing students was 41.17. The findings revealed that most students had positive views of the nursing profession, which were in line with findings from earlier research [ 17 , 27 ]. However, the low calling group accounting for 30.3% of the total participants, which revealed that nurses' calling was lower than that of other care professionals as a result of their subpar remuneration and working circumstances [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results were similar to another Chinese research [ 26 ], which indicated that the average score of calling among nursing students was 41.17. The findings revealed that most students had positive views of the nursing profession, which were in line with findings from earlier research [ 17 , 27 ]. However, the low calling group accounting for 30.3% of the total participants, which revealed that nurses' calling was lower than that of other care professionals as a result of their subpar remuneration and working circumstances [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…A longitudinal study found a significant positive correlation between calling and career preparation [ 16 ]. It has also been shown in other studies that there is a connection between calling, professional identity [ 17 ], and career commitment [ 18 ] among college students.…”
Section: Introductionmentioning
confidence: 74%
“…This nding was in line with the ndings of previous literature. For example, [37] veri ed the mediating effect through a cross-sectional study which found the positively association between calling and moral identity. The ndings of the study add strong evidence that calling can be a signi cant stimulus for enhancing moral identity.…”
Section: Discussionmentioning
confidence: 96%
“…The calling of nursing and nursing professionalism have been reported to be motivating and applied to clinical sites to care for patients with COVID-19 [ 24 ]. Further, nurses’ images were delivered to people through the media, affecting not only the public but also nursing students’ awareness and attitudes toward the satisfaction of nursing majors and nursing professionalism [ 25 ]. Previous studies have confirmed a significant correlation between nursing students’ consciousness of calling and nursing professionalism [ 20 ]; however, no studies have confirmed the mediating effect of consciousness of calling on the relationship between self-leadership and nursing professionalism.…”
Section: Introductionmentioning
confidence: 99%